2021
DOI: 10.3390/su13169316
|View full text |Cite
|
Sign up to set email alerts
|

A Trust-Based Model for the Adoption of Smart City Technologies in Australian Regional Cities

Abstract: This paper explores the role of stakeholders’ trust in the adoption of smart city technologies, leading to the identification of the critical determinants for adopting smart city technologies in Australian regional cities. A comprehensive review of the related literature has been conducted. Such a review leads to the development of a trust-based research model for investigating the importance of trust in technology and its adoption. This model is then tested and validated with the use of a structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The findings generated support for all the hypothesized paths in the study. The finding that perceived usefulness and perceived ease of use positively influence e-government adoption aligns with extensive prior research grounded in the TAM such as Mensah et al (2023), Pour et al (2022, Al-Rahmi et al (2022). Their empirical results demonstrate that citizens' favorable perceptions regarding the usefulness and ease of use of various e-government services lead to greater acceptance and usage intentions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings generated support for all the hypothesized paths in the study. The finding that perceived usefulness and perceived ease of use positively influence e-government adoption aligns with extensive prior research grounded in the TAM such as Mensah et al (2023), Pour et al (2022, Al-Rahmi et al (2022). Their empirical results demonstrate that citizens' favorable perceptions regarding the usefulness and ease of use of various e-government services lead to greater acceptance and usage intentions.…”
Section: Discussionsupporting
confidence: 80%
“…The results showed that citizens' who trusted e-government services and their provision by the government were more willing to use such services. Similarly, Neupane et al (2021) examined trust factors in the adoption of smart cities and trust been a significant predictor of adoption smart city technologies from the perspective of ICT professionals in Australia. Therefore, based on the foregoing, it is hypothesized that: H3.…”
Section: Theoretical Background and Hypothesis Formationmentioning
confidence: 99%
“…The degree to which consumers consider smart city technologies or services to be a safe platform for storing and sharing personal data is known as perceived security [96]. The adoption of innovations is hindered by a lack of perceived security [97] and external pressure and perceived information security influence trust in smart city technologies [98]. Previous research on this topic has been conducted in several fields such as cloud computing, education, e-banking, and e-governance services [99][100][101][102].…”
Section: Perceived Security (Ps)mentioning
confidence: 99%
“…Put succinctly, adoption‐based articles primarily conduct empirical investigation of the factors that affect the degree of acceptance of the concerned technology. Indeed, there has been growing literature that has empirically validated the factors impacting the adoption of IoT devices in different contexts, including supply chain management (Lee & Lee, 2015; Tu, 2018), healthcare (Arfi et al, 2021; Prayoga & Abraham, 2016), agriculture (Shi et al, 2022; Strong et al, 2022), smart homes (Mital et al, 2018; Shin et al, 2018), education (Almaiah et al, 2022; Gökçearslan et al, 2022) and smart cities (Neupane et al, 2021; Sepasgozar et al, 2019). However, few studies attempted to synthesize the extant literature on IoT adoption into a systematic review.…”
Section: Introductionmentioning
confidence: 99%